ANALISIS PERHITUNGAN, PENCATATAN DAN PELAPORAN PAJAK PENGHASILAN PASAL 25 PADA CV. VENUS KUMERSOT RAYA - Sejanto, Triastuty Wulanjune; Elim, Inggriani; Tirayoh, Victorina Z. (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
Income Tax Article 25 (Income Tax Article 25) shall be installment of income tax in installments. The objective is to alleviate the taxpayerâs burden, since the tax payable must be paid within one year. This payment must be done alone and can not be represented. The purpose of this study to find out how the calculation, recording and reporting of Income Tax Article 25 on the CV. Venus Kumersot Raya. The method of analysis used in this research is descriptive with qualitative approach. The results of this study indicate that the calculation of Income Tax Article 25 conducted by the company has not been in accordance with the Act. Taxation No.36 Year 2008. This is evidenced by companies that do not allow for the recording and reporting of Income Tax Article 25 that has been done by the company every month is in accordance with applicable taxation provisions. CV. Venus Kumersot Raya has made taxes and taxes in the tax year of the 1771 Annual Tax Return, the berlin company may make appropriate tax payments on taxes and taxes in accordance.Keywords: Calculation, Recording, Reporting, Income Tax Article 25